Potency of Coconut Shell Biochar to Remediate Ion Chromium in Contaminated Water - Faris, Salman; Titah, Harmin Sulistiyaning; Pratikno, Herman (The Journal of Experimental Life Science, 2023)
Many heavy metals contaminate our environment, including chromium (Cr(VI) contaminated water. The aim of this study was to determine the removal of ion Cr(VI) using the coconut shell biochar. Biochar activation processes were conducted at 350℃ and 550℃. The characteristic tests of biochar were conducted, such as testing for moisture, ash, volatile, and carbon content. Additionally, a scanning electron microscope was also performed. The remediation test was carried out on a laboratory scale with a batch system. The variables were the mass of coconut shell biochar (0, 8, and 16 r) and the time of process were 0, 30, and 60 min. Based on the results, the characteristics of coconut shell biochar showed a high carbon content, which reaches 80.4% for activation temperature at 500℃ and 73.02% for 350℃. Coconut shell biochar can reduce ion Cr(VI) in water; it reached 73.78% to 88.15%. The percentage of Cr(VI) reduction in water reached 88.15% using biochar that was activated at a temperature of 350℃ and a mass of 16 g at a detention time of 60 min. In conclusion, coconut shell biochar has good potential to reduce chromium in water. Keywords: Biochar, Chromium, Coconut Shells, Remediation.